Peran Strategis Ilmu Linguistik dalam Pembelajaran Bahasa Arab di Perguruan Tinggi - Yahya, Mumtaz (April & October, 2026)
Linguistics holds an essential role in Arabic language instruction at the university level, as it supports the development of structured and meaningful linguistic understanding. Learning Arabic involves not only the acquisition of language skills but also a thorough comprehension of the language system, including phonology, morphology, syntax, and semantics. This study aims to explore how linguistic studies contribute to the enhancement of students’ Arabic language competence in higher education. The research adopts a qualitative approach through a library-based method by examining scholarly literature related to Arabic linguistics and Arabic language education. The findings reveal that incorporating linguistic perspectives into the learning process enables students to gain a deeper understanding of Arabic grammatical structures, reduces language-related errors, and strengthens analytical language abilities. In addition, a linguistic approach facilitates the design of more effective learning strategies that emphasize conceptual understanding. Consequently, linguistics serves as a crucial theoretical foundation for Arabic language learning in higher education to promote the continuous development of students’ language competence.